Javanese Islamic Moderation of Sunan Kalijogo, Harmonization of Islamic and Javanese Teachings (Aggregation of Culture and Ideology) - Zakiyah, Ermita; Magfiroh, Norma Hasanatul; Sarif, Nur Ikhsan Mahmudi (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 3 No 1 (2022): Proceeding of International Conference on Engineering, Technology, and Social Sciences, 2023)
Islam came in a condition where Javanese culture was rooted in society. As a new teaching, Islam is easy to accept, this is ironic because Islamic teachings are very different from what has become culture in Java. With the arrival of the Kalijaga Sunan, Javanese culture and Islamic teachings were introduced into a complementary aggregation so as to form a harmony between culture and ideology. Reflecting on this, the authors reveal that the purpose of this study is to find out how the approach to introducing Islam to Javanese society was used by Sunan Kalijaga, how the established ritual was incorporated into Islamic teachings. The research method used in this paper is historia library research. This research concludes that the teachings of Islam and Java have a positive aggregation between culture and ideology, this is stated by Sunan Kalijaga which is explicitly different from other Walisongo's teachings, and opens up that Sunan Kalojaga's Javanese Islam is in line with Islam.